# How do i derive the formula for "E" in terms of P & R using the equations E= I x R & P= I x E

*print*Print*list*Cite

### 2 Answers

Solve for I on P = I x E.

Since, E is being multiplied on right side, we divide both sides by E.

`(P/E) = (I x E)/E`

Cancel common factor on top and bottom of right side.

`P/E = I` or `I = P/E`

Replace the I on E = I x R by what we got.

`E = (P/E) x R`

Multiply both sides by E.

`E x E = E x (P/E)x R`

`E^(2) = P x R`

Take the square root of both sides.

`E = sqrt(P x R)`

``

**Eliminate I from both equation (only I prsent in both equation)**

since `E=IxxR`

`E/R=I` (i)

also

`P=ExxI`

`P/E=I` (ii)

from (i) and (ii) ,we have

`E/R=P/E`

cross multiply

`E^2=PxxR`

which is required formula.